Perancangan Video Promosi Cat Aksritex Menggunakan Media YouTube - Zulfiqar Bima Bagaskara; Putra Uji Deva Satrio (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2019)
Aksritex paint is one of the textile paints. It was originally created by Ms. Nanik (an art teacher) in 2017. Aksritex paint was first promoted through